The Online Eunuch as a ‘CyborgianTrans’ Figuration: De-stabilising Gendered Meanings and Subjectivities - Kaur, Surinderpal (SARE: Southeast Asian Review of English, 2017)
Like the materially bounded body, the representation and reproduction of the online body is subject to ambiguities and multiplicities. Online discussion boards provide spaces that not only reinforce traditional norms and practices related to gender and sexuality but also provide spaces that highlight the transgressions of these traditional norms and practices. This paper aims to explore the ways in which the category of ‘eunuch’ is reimagined in multiple subjectivities in online interactions, specifically by examining how the body of a eunuch is constituted in online discussion boards. Importantly, the paper also proposes the analytical construct of the “CyborgianTrans” in order to reveal the multiplicities and ambiguities inherent in online self-representations of eunuch identities.